2021
DOI: 10.1111/ane.13573
|View full text |Cite
|
Sign up to set email alerts
|

Glymphatic dysfunction in isolated REM sleep behavior disorder

Abstract: Objectives This study aimed to evaluate glymphatic‐system function in patients with isolated rapid eye movement sleep behavior disorder (iRBD) in comparison with healthy controls by using diffusion tensor imaging (DTI) along the perivascular space (DTI‐ALPS) method. We hypothesized that patients with iRBD may show glymphatic‐system dysfunction. Methods We retrospectively enrolled 18 patients with iRBD and 18 age‐ and sex‐matched healthy controls. All participants underwent DTI magnetic resonance imaging (MRI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“… Diagram depicting how the diffusion tensor image analysis along the perivascular space (DTI-ALPS) index is calculated ( 16 ). …”
Section: Methodsmentioning
confidence: 99%
“… Diagram depicting how the diffusion tensor image analysis along the perivascular space (DTI-ALPS) index is calculated ( 16 ). …”
Section: Methodsmentioning
confidence: 99%
“…These studies suggest the promise of the DTI-ALPS index as an imaging marker for assessing cognitive impairment. Two other researches on sleep disorders found that the DTI-ALPS index was significantly lower in patients with obstructive sleep apnea (OSA) and isolated rapid eye movement sleep behavior disorder (iRBD) than in healthy controls ( 94 , 95 ).…”
Section: Imaging Of Brain Glymphatic Systemmentioning
confidence: 99%
“…To further understand the effects of sleep deprivation on Aβ clearance, a clinical trial in 20 healthy controls who underwent 31 h of sleep deprivation showed that Aβ was increased by 5% in the hippocampus, the parahippocampus, and the thalamus ( 65 ). Moreover, a recent study that tracked the REM phase in patients who experienced poor sleep found that the index of diffusion tensor imaging analysis along the perivascular space was significantly lower in patients than in healthy controls, which indicated glymphatic dysfunction ( 66 ). Thus, we speculate that the GS is intimately linked to various aspects of sleep.…”
Section: The Glymphatic System and Sleep Disordersmentioning
confidence: 99%